Suntik Hormon Meningkatkan 20lbs Masa Otot? Natural vs Steroid - Rizki Oktario (AGUSPATI RESEARCH INSTITUTA, 2023)
themselves are derivative products of the male sex hormone, namely Testosterone. Testosterone is a male sex hormone that affects hair quality, bone density, voice, mood, sexual level, protein absorption for muscle formation, and of course, good protein absorption can form more muscle mass. This study report uses a descriptive qualitative method by taking notes because of what was obtained by listening to the oral narrative from Jeff Nippard's YouTube channel entitled